Yesus Inang Tuak: Kajian Kristologis Postkolonial Feminis Dalam Upaya Merevitalisasi Lapo Tuak - Tiffany Tamba (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2021)
The purpose of this article is to explore the reflection of feminist postcolonial Christology in the paintings of Emmaus – Emmanuel Garibay, which is creative, imaginative, provocative, and born from the painter's existential experience. I explored the views of theologians and artists about the painting to transform my thoughts as a Batak generation regarding the Christology doctrine, which is attached to human taste and culture, which Emanuel Gerrit Singgih called Jesus Inang tuak. Using the critical analysis, I found that the Christological reflection of Emmaus - Garibay's painting invites people to rethink the images of the life and work of Christ's ministry in the world using a postcolonial perspective. Jesus Inang tuak reflects feminist postcolonial Christology seeing Christ post-easter, which breaks the patriarchal view of Jesus and life and transforms the cultural community of society (especially the Batak people). This research will explore three primary aspects: the pros and cons of lapo tuak, the meaning of Emmaus' painting, and the reflection of feminist postcolonial Christology to revitalize the Batak people's lapo tuak.